(untitled) (Journal of Parents and Teachers, 1995)
Family relationships have improved, although at times old patterns resurface, generating doubts about change. The loss of traditional values and the use of irony as harmful criticism are highlighted. Humility and truth are essential to resolve conflicts and maintain respect for privacy.